Remote effects of acute kidney injury in a porcine model - Gardner, David S.; de Brot, Simone; Dunford, Louise J.; Grau-Roma, Llorenc; Welham, Simon J.M.; Fallman, Rebecca; O'Sullivan, Saoirse; Oh, Weng; Devonald, Mark A.J. (American Physiological Society, 2016)
Background: Acute Kidney Injury (AKI) is a common and serious disease with no specific treatment. An episode of AKI may affect organs distant to the kidney, further increasing the morbidity associated with AKI. The mechanism of organ cross-talk after AKI is unclear. The renal and immune systems of pigs and humans are alike. Using a preclinical animal (porcine) model, we test the hypothesis that early effects of AKI on distant organs is by immune cell infiltration leading to inflammatory cytokine production, extravasation and edema. Study Design: In 29 pigs exposed to either sham-surgery or renal ischemia-reperfusion (control, n=12; AKI, n=17) we assessed remote organ (liver, lung, brain) effects in the short-(from 2 to 48h reperfusion) and longer-term (5 weeks later) using immunofluorescence (for leucocyte infiltration, apoptosis), a cytokine array, tissue elemental analysis (electrolytes), blood hematology and chemistry (e.g. liver enzymes) and PCR (for inflammatory markers). Results: AKI elicited significant, short-term (~24h) increments in enzymes indicative of acute liver damage (e.g. AST:ALT ratio; P=0.02) and influenced tissue biochemistry in some remote organs (e.g. lung tissue [Ca++] increased; P=0.04). These effects largely resolved after 48h and no further histopathology, edema, apoptosis or immune cell infiltration was noted in liver, lung or hippocampus in the short- and longer-term. Conclusions: AKI has subtle biochemical effects on remote organs in the short-term including a transient increment in markers of acute liver damage. These effects resolved by 48h and no further remote organ histopathology, apoptosis, edema or immune cell infiltration was noted.